Technical feasibility and safety of transluminal antegrade dilation for hepaticojejunostomy stricture using a novel fine-gauge electrocautery dilator (with video) - Ogura, Takeshi; Nishioka, Nobu; Yamada, Masanori; Yamada, Tadahiro; Ueno, Saori; Matsuno, Jyun; Ueshima, Kazuya; Yamamoto, Yoshitaro; Okuda, Atsushi; Ashida, Reiko; Higuchi, Kazuhide (Endoscopy International Open, 2020)
Background and study aims A novel fine-gauge electrocautery dilator (ED) has recently become available in Japan. The current study evaluated the safety and feasibility of transluminal antegrade dilation for hepaticojejunal stricture (HJS) using this novel ED.Patients and methods Patients who with complicated HJS were retrospectively enrolled. The primary and secondary endpoints of this study were rates of technical success defined as functional antegrade HJS dilation using the novel ED and types of adverse events, respectively. A total of 22 patients were enrolled. Among them, six were treated using an enteroscopic approach due to the absence of bile duct dilation or patient refusal to undergo EUS-HGS. Therefore, 16 patients underwent EUS-HGS.Results The procedure was successful in 15 of 16 patients (93.8 %). The contrast medium flowed from the intrahepatic bile duct to the intestine of 14 of 15 patients (93.3 %). The resolution rate of HJS was 13 of 14 (92.9 %) at 6 months.Conclusion Our technique might offer a new option with which to treat HJS, although a prospective study with long-term follow-up is needed.